El empleo de productos reciclables para la elaboración de material didáctico en el área de ciencias naturales de las niñas del quinto grado de educación básica de la escuela Eliseo Álvarez, parroquia San Sebastián, cantón y provincia de Loja, periodo lectivo 2012-2013 - Sánchez Ramírez, Paúl Alejandro (2014)
This educational research reviews the complexity of the educational portion passing constantly changing , different methods on the use of recyclable products for the development of training materials in the area of Natural Sciences School girls ' Eliseo Alvarez ' investigates this research aims to know whether to use recyclable products contributes to the learning of Natural Sciences. In the theoretical part will be contained on recyclable products and training materials for the Department of Natural Sciences , I will use a qualitative description research and information and will be raising a proposal. The study population will be girls and school teachers " Eliseo Alvarez " The research results show that the use of teaching materials made from recycled products if influences learning of Natural Sciences. The target was raised to analyze how the use of educational materials developed based recyclable products contributes to improving the quality of learning in the area of Natural Sciences of girls in the fifth grade of Basic Education "Eliseo Alvarez" School; specific objectives were constructed to determine the importance of having the use of recyclable products to develop them educationally as a medium in the teaching of natural sciences. With the tabulation and statistical development came to their conclusions and recommendations necessary to improve the quality of learning using recyclable for teaching natural science.